Realizing the UN Declaration on the Rights of Indigenous Peoples: triumph, hope, and action - Joffe, Paul; Hartley, Jackie; Preston, Jennifer (Purich Pub., 2010)
Adopted by the UN General Assembly on 13 September 2007, the United Nations Declaration on the Rights of Indigenous Peoples affirms the “minimum standards for the survival, dignity and well-being of the indigenous peoples of the world.” The Declaration responds to past and ongoing injustices suffered by Indigenous peoples worldwide. It provides a strong foundation for improved relationships with states, and for the full recognition of the inherent rights of Indigenous peoples. Despite this, Canada was one of the few countries to oppose the Declaration. The contributors to this collection analyze the development of the Declaration, recall the triumph of its adoption, and illustrate the hopes and actions for its implementation. The discussion moves beyond Canadian borders to the international stage, providing accessible information and guidance on the Declaration and how it can be used to advance human rights. Policy makers, Indigenous communities, politicians, academics, lawyers, human rights advocates, NGOs, and anyone interested in the significance of the Declaration will find this to be a valuable resource. Contributors include Indigenous leaders, legal scholars and practitioners, state representatives, and representatives from NGOs, with extensive knowledge of and experience in Indigenous peoples’ human rights law, policy, and practice.
Le texte de McKay, M. C. et Benjamin, C. (2010). A vision for fulfilling the indivisible rights of Indigenous women a été donné en lecture au cours POL4105.
Keywords: 2000 à aujourd'hui; 2000-2009; ONU; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; droits des personnes autochtones; histoire et politique; justice sociale; pol4105; premier cycle; premiers peuples; premières nations; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Sous les yeux de l’Occident : recherches féministes et discours coloniaux - Mohanty, Chandra Talpade (Genre, postcolonialisme et diversité de mouvements de femmes, 2010)
Note de l’éditeur Traduit de l’anglais. Texte original: Under Western eyes : Feminist scholarship and colonial discourses. In Feminism without borders : Decolonizing theory, practicing solidarity. 17-42. Durham : Duke University Press. 2003. Tous droits réservés. Reproduit avec l’aimable autorisation de l’éditeur. Parution originale 1986.
Keywords: EDI; afro-féminisme; approches et analyses; cours; discipline; discours dominant; droits des femmes*; ethnocentrisme; féminisme africain; féminisme autochtone; féminisme du sud; féminisme décolonial; féminisme transnational; histoire et politique; injustices épistémiques; inégalités; justice sociale; militance; patriarcat; phi4336; philosophie politique; pol4212; pratiques féministes; premier cycle; privilèges; racisme; sciences humaines; sociologie; sujet du féminisme; système colonial; systèmes d'oppressions; thématiques; théorie féministe; violences

Pour une meilleure compréhension des particularités de la violence familiale vécue par les femmes autochtones au Canada - Montminy, Lyse; Brassard, Renée; Jaccoud, Mylène; Harper, Elizabeth; Bousquet, Marie-Pierre; Leroux, Shanie (Nouvelles pratiques sociales, 2010)
La violence conjugale en milieu autochtone présente des particularités qui demeurent trop souvent ignorées ou confondues avec celles d’autres groupes de femmes violentées au Canada. Cet article rapporte les résultats d’une analyse de documents produits au cours des trois dernières décennies afin de dégager les principales caractéristiques de cette problématique. Cette analyse suggère que la notion de violence familiale doit être privilégiée à toute autre et que la violence conjugale dont les femmes autochtones sont victimes se distingue tant par ses formes, sa fréquence que par sa gravité.Aspects that are unique to conjugal violence as experienced by Aboriginal women are often ignored and confounded with those of other groups of abused women in Canada. This article presents an analysis of documents from different sources of knowledge that have been produced over the last three decades in order to identify distinctive dimensions of this problem. The analysis points to the significance of the notion of family violence over other terms that are used to describe conjugal violence and to the different facets of Aboriginal women’s experiences of violence with regards to prevalence, severity and forms of violence.
Keywords: amériques; analyse documentaire; approches et analyses; canada; cours; discipline; femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; travail social; trs3500; violences; violences conjugales